Serum interleukin-6 and C-reactive protein are associated with survival in melanoma patients receiving immune checkpoint inhibition. Issue 1 (23rd June 2020) - Laino, Andressa S; Woods, David; Vassallo, Melinda; Qian, Xiaozhong; Tang, Hao; Wind-Rotolo, Megan; Weber, Jeffrey
Abstract : Background: Inflammatory mediators, including acute phase reactants and cytokines, have been reported to be associated with clinical efficacy in patients with melanoma and other cancers receiving immune checkpoint inhibitors (ICI). Analyses of patient sera from three large phase II/III randomized ICI trials, one of which included a chemotherapy arm, were performed to assess whether baseline levels of C-reactive protein (CRP), interleukin-6 (IL-6) or neutrophil/lymphocyte (N/L) ratios were prognostic or predictive. Patients and methods: Baseline and on-treatment sera were analyzed by multiplex protein assays from immunotherapy-naïve patients with metastatic melanoma randomized 1:1 on the Checkmate-064 phase II trial of sequential administration of nivolumab followed by ipilimumab or the reverse sequence. Baseline sera, and peripheral blood mononuclear cells using automated cell counting, were analyzed from treatment-naïve patients who were BRAF wild-type and randomly allocated 1:1 to receive nivolumab or dacarbazine on the phase III Checkmate-066 trial, and from treatment-naïve patients allocated 1:1:1 to receive nivolumab, ipilimumab or both ipilimumab and nivolumab on the phase III Checkmate-067 trial. Results: Higher baseline levels of IL-6 and the N/L ratio, and to a lesser degree, CRP were associated with shorter survival in patients receiving ICI or chemotherapy. Increased on-treatment levels of IL-6 in patients on the Checkmate-064 study were also associated with shorter survival. IL-6 levels from patients on Checkmate-064, Checkmate-066 and Checkmate-067 were highly correlated with levels of CRP and the N/L ratio. Conclusion: IL-6, CRP and the N/L ratio are prognostic factors with higher levels associated with shorter overall survival in patients with metastatic melanoma receiving ICI or chemotherapy in large randomized trials. In a multi-variable analysis of the randomized phase III Checkmate-067 study, IL-6 was a significant prognostic factor for survival.